2008
DOI: 10.1093/molehr/gan008
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin F2-alpha receptor regulation in human uterine myocytes

Abstract: Investigations of the modulation of prostaglandin F(2alpha) receptor (FP) expression in primary cultures of human uterine myocytes showed that FP mRNA expression was reduced by progesterone, unaltered by cAMP (8-bromo cAMP or forskolin), but increased by the PKA antagonist H89. Interleukin (IL)-1beta, tumour necrosis factor-alpha and oxytocin increased FP mRNA expression and IL-6 and prostaglandin E(2) reduced FP mRNA expression. The changes in FP protein levels were similar to the mRNA responses. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…For example, we and others have demonstrated that IL-1β, TNFα and IL-6 can increase prostaglandin production by amnion, decidua and myometrium [11, 21, 22, 70, 73, 138140, 155, 175, 198, 199, 202, 294, 325]. PTGS2/COX2 is a rapidly inducible enzyme with reported increased expression in association with labor in myometrium [5, 6, 44, 54, 67, 115, 136, 233, 278, 284, 289, 306] and the uterine cervix [26, 67, 132, 186, 230, 297, 313, 330, 331].…”
Section: Discussionmentioning
confidence: 99%
“…For example, we and others have demonstrated that IL-1β, TNFα and IL-6 can increase prostaglandin production by amnion, decidua and myometrium [11, 21, 22, 70, 73, 138140, 155, 175, 198, 199, 202, 294, 325]. PTGS2/COX2 is a rapidly inducible enzyme with reported increased expression in association with labor in myometrium [5, 6, 44, 54, 67, 115, 136, 233, 278, 284, 289, 306] and the uterine cervix [26, 67, 132, 186, 230, 297, 313, 330, 331].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, NF‐κB leads to inflammatory cell migration into the myometrium, with a consequent marked increase in local cytokine concentrations. These cytokines would then stimulate synthesis of prostaglandins [47, 48], induce calcium entry into myometrial smooth‐muscle cells [49], increasing their contractility, and stimulate phosphodiesterase activity, leading to a decrease in cAMP (adenosine monophosphate) concentrations [50].…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin is synthesized in the neurohypophysis and enhances secretion of prostaglandin F2α (PGF2α) in endometrial stroma and glandular cells and expression of the PGF2α receptor. 76,77 Systemic oxytocin administration in the follicular phase increases the amplitude of uterine contractions and reverses the pressure gradient from fundal cervical to cervical fundal as measured with IUP. 23 Vasopressin, another nonapeptide synthesized in the neurohypophysis, mediates its effects through subtype receptors including the V1A subtype receptor 78 found in the uterus.…”
Section: Potential Therapeuticsmentioning
confidence: 99%